If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = 3(x + -30) Reorder the terms: 2x = 3(-30 + x) 2x = (-30 * 3 + x * 3) 2x = (-90 + 3x) Solving 2x = -90 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2x + -3x = -90 + 3x + -3x Combine like terms: 2x + -3x = -1x -1x = -90 + 3x + -3x Combine like terms: 3x + -3x = 0 -1x = -90 + 0 -1x = -90 Divide each side by '-1'. x = 90 Simplifying x = 90
| 4x-5=x+17 | | p(x)=x^2+15x+50 | | 5x+(3x+24)=8+6x | | 12-(3x-7)=2x-(x-1) | | -7(x+5)+3(x-6)= | | f-1(2)= | | 5-(8-x)=3-(x-6) | | -(v-2)=-4(v-8)-8v | | x(x+3)=-8 | | (2x^2)+5x+8=0 | | 16z=-128 | | 7-q-q-2q=80 | | 4p-25=-32+5p | | 4p-12=-3+p | | -7x-10x=-85 | | 4x-10x=70 | | -5x-15=-95 | | -60=3+9x | | (3x^2)-5x-7=0 | | (2x^2)+8x=0 | | 1+x^2=0 | | (2x^2)-7x-1=0 | | 27a^3x^4-8x=0 | | 8+2x=x+40 | | 3y+24+6-2=33 | | -28+4=0 | | ln(x+1)ln(x)+ln(x^2)=1 | | ln(x+a)ln(x)+ln(x^2)=1 | | 53-2x=5x | | 11x-10=54 | | 6p^2+25-119=0 | | (6a^3+6a^2-7)+(5a^3-6a+8)= |